Design and fabrication of a new ultrasonic device and its application for drug delivery - Zhang, Hong Ye (2008)
In this research, two new prototype devices, namely ‘A’ and ‘B’, were developed based on flat flextensional ultrasound transducers. Device ‘A’ that has a single flat flextensional transducer was designed to verify the feasibility of such a transducer for the drug delivery applications. Device ‘B ’ which has dual flat flextensional transducers (named Transducer ‘1’ and Transducer ‘2’) was developed based on the acoustic interference principle in order to generate more acoustic power with lower input electrical power.